Management of Rapidly Ascending Driveline Tunnel Infection. Issue 11 (7th October 2015) - Rubinfeld, Gregory; Levine, Jamie P.; Reyentovich, Alex; DeAnda, Abe; Balsam, Leora B.
Abstract We present a case of rapidly ascending left ventricular assist device driveline and tunnel infection in a patient with a long length of driveline buried beyond the distal velour coating. Device salvage with radical debridement, exit site relocation, and local tissue advancement is described. The findings in this case suggest that the interface between nonvelour covered driveline and subcutaneous tissue can become the nidus of a virulent ascending infection because of poor tissue ingrowth.